FROM IDEA TO ACTION TOWARDS SOCIAL EDUCATION IN EUROPE. EVOLUTION OF PEDAGOGY AND SOCIAL EDUCATION - Añaños-Bedriñana, Fanny (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
This article aims offering on one side: a historical development framework in Europe specially in Germany as well as in Spain; and by another side: A theorical space –Going from Scientific methods and references outlined by today’s tendency on pedagogy and social education.It also craves to understand the origins of pedagogy and social studies at the same time, thus they bring both black and grey ideas for answering through social- educational action based on praxis and evidence without missing the educational plan and sense of human liberation perspective, education oriented towards life quality transformation.What History became into today’s social education awareness, and pedagogy as a science in constant evolution, opened to new approaches brought from features and details of each context either from people or moment of time,  as an attempt to accomplish challenges, to specific issues or to promote regular educators aiming for changes and quality life improvement.